Penerapan Senam Otak dan Relaksasi Otot Progresif terhadap Tingkat Kecemasan pada Lembaga Pembinaan Khusus Anak - Putra, Sumitro Adi; Syokumawena, Syokumawena; Sulistini, Rumentalia (Pusat Penelitian dan Pengabdian kepada Masyarakat, Politeknik Kesehatatan Kemenkes Palembang, 2024)
Stress is a physical and psychological response due to internal pressure which can disrupt balance and cause tension. There is positive stress, called eustress, if the individual can control the stressor very well. However, there is also stress that is negative in nature, called distress, that is, the individual cannot overcome the stressor they are experiencing. Considering that LPKA life is not conducive and their developmental age is still children, the children assisted by LPKA Class I Palembang have a tendency to experience stress. The situation of correctional institutions is that most of them exceed their proper capacity. This condition is also a source of stress for the inmates. Activities to reduce anxiety levels can be used in various ways, such as brain exercises and relaxation techniques. This community service activity involved 50 juvenile prison participants. Participants were divided into 2 groups where group 1 was given brain exercise therapy and group 2 was given muscle relaxation. The anxiety results were evaluated and there was a decrease in anxiety level.